A Critical Examination of Anti-Racist Education - Mansfield, Earl; Kehoe, John (Canadian Journal of Education/Revue canadienne de l'éducation, 1994)
Multicultural education has been the subject of intense criticism since the early 1970s. Most criticism has come from the advocates of anti-racist education. At the same time, anti-racist education has been subjected to very little scrutiny. This paper examines some conceptual, empirical, and political limitations of anti-racist education. Most educators consider the current curriculum to be apolitical. Although it is the case that all education is political education, anti-racist education is viewed as being too political. Anti-racist education tends to be reductive—victims of discrimination are usually referred to as “black,” whereas perpetrators are “white” — and narrowly conceived to refer only to institutional racism. Finally, many of the anti-racist interventions reported show negligible and even negative results. Depuis le début des années 70, l’éducation multiculturelle fait l’objet de vives critiques, surtout de la part des partisans d’une éducation antiraciste. Pour sa part, l’éducation anti- raciste a été très peu commentée. Dans cet article, les auteurs examinent certaines lacunes conceptuelles, empiriques et politiques de l’éducation antiraciste. La plupart des éducateurs estiment que les programmes d’études actuels sont apoli- tiques. Bien qu’en fait toute éducation soit politique, l’éducation antiraciste est considérée comme trop politique. L’éducation antiraciste a tendance à être réductionniste — les vic- times de discrimination étant habituellement désignées comme des “Noirs” et les coupables comme des “Blancs” — et à ne s’occuper par définition que du racisme institu- tionnel. En outre, un grand nombre des interventions antiracistes signalées donnent des résultats négligeables et parfois même négatifs.